Design and Development of a Web-Based Virtual Programming Laboratory for Information Systems Education - David Naista; Ghifar Javad H Aziz (PT. Tech Cart Press, 2026)
This study presents the design, development, and evaluation of a web-based virtual programming laboratory for Information Systems education. The research addresses key limitations of traditional programming laboratories, including limited accessibility, dependency on physical infrastructure, and restricted opportunities for continuous practice. To overcome these challenges, a virtual laboratory system is developed using a web-based architecture that enables users to perform programming activities anytime and anywhere. The system adopts a layered architecture consisting of presentation, application, execution, and data layers. Core features include a web-based code editor, a server-side execution engine, structured learning modules, and real-time output visualization. The system is implemented as an integrated platform that supports interactive programming practice and instructional content delivery. The evaluation is conducted through functional testing, usability assessment, and performance analysis. The results indicate that the system operates reliably, with all core functionalities performing as expected. Usability evaluation shows that the system provides a clear interface, efficient navigation, and high accessibility across devices. The performance analysis demonstrates that the system supports real-time interaction with acceptable response time. From a pedagogical perspective, the system enhances learning effectiveness by enabling continuous practice and providing immediate feedback. The structured learning modules support progressive skill development and improve problem-solving ability. The findings confirm that the developed virtual laboratory provides an effective and scalable solution for programming education. The system contributes to advancing digital learning environments and offers practical implications for higher education institutions.